VARIABILITAS SPASIAL HUJAN DI WILAYAH UPT PSDA DI MALANG - Indarto Indarto; Askin Askin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
This study show the spatial variabilit of rainfall (monthly and annual) rainfall in the area of technical implementation unit of water resources management (UPT-PSDA) in Malang. Administrative area of UPT PSDA in Malang include Malang regency, Malang city, Batu, Blitar Regency, Tulungagung Regency, and Trenggalek Regency. Daily rainfall  data from 88 pluviometers spread around the areas are used as main input. The research procedures consist of : (1) data pre-analysis; (2) the analyses using ESDA tools (Histogram, voronoi, QQ-Plot); (3) interpolation by using IDW method; (4) producing a thematic map; and (5) interpretation.  Analysis using the histogram, voronoi–maps and normal QQ-plots tools illustrates more detail the spatial variability of the monthly and annual rainfall around the regions. Interpolation produces a thematic map of mean monthly-rainfall, between 100 – 400 mm/month. The spatial distribution of annual rainfall was illustrated by a thematic show the average-annual-range from 1000 – 4000 mm/year. Keywords: spatial variability, rainfall, ESDA, IDW, monthly, annual rainfall